(untitled) (Ustozlar uchun, 2025)
Abstract. Sign interpreting, which involves transferring meaning between a spoken language and a signed language, represents a highly specialized form of simultaneous interpreting. Unlike spoken language interpreting, sign interpreting operates across modalities – auditory - vocal and visual – gestural - requiring unique cognitive, linguistic, and ethical competencies. This paper examines sign interpreting as a type of simultaneous interpreting by exploring its linguistic foundations, cognitive processes, strategies, challenges, and professional practices. Drawing on linguistic and interpreting studies, it highlights how simultaneity in sign interpreting presents both opportunities for immediate communication and difficulties related to cognitive load, spatial grammar, and modality constraints. The article also discusses the implications for interpreter training and professional standards.